How Do University Students’ Perceptions of the Instructor’s Role Influence Their Learning Outcomes and Satisfaction in Cloud-Based Virtual Classrooms During the COVID-19 Pandemic? - Wang, Rong; Han, Jiying; Liu, Chuanyong; Xu, Hongji (Frontiers in Psychology, 2021)
This study examined the relationships between the role of instructors in university students’ learning outcomes in cloud-based classrooms in the COVID-19 outbreak. The results of an online questionnaire survey of 7,210 university students in mainland China revealed that students’ perceived learning outcomes and learning satisfaction were positively related to instructor innovation, and negatively related to instructor performance. Instructional support was positively related to students’ perceived learning outcomes but not directly related to learning satisfaction. Students’ academic self-efficacy mediated the influence of instructional support and instructor innovation on their perceived learning outcomes and learning satisfaction. The results contribute to knowledge about the role of instructors in students’ learning outcomes in higher education, and provide evidence for facilitating a favorable learning environment and desirable learning outcomes especially in cloud-based virtual classrooms.